2019
DOI: 10.1111/agec.12545
|View full text |Cite
|
Sign up to set email alerts
|

Moral hazard and subsidized crop insurance

Abstract: Along with adverse selection, moral hazard is one of the major hurdles that private and public insurance plans must contend with. Moral hazard occurs if risks are endogenous to a producer's behavior and if the insurer is unable to properly monitor the insured. We review the role of moral hazard in the US crop insurance program. We conduct an empirical analysis of one important aspect of the US crop insurance program—prevented planting. This provision provides indemnity payments if conditions are not suitable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Thus, what is "catastrophic" is less useful as an absolute measure and more related to specific characteristics of the crop/region in question, keeping in mind that these conditions may be changing due to climate change. 6 Other international negotiations are also affecting development of (and support for) risk management policy tools. Specifically, the 2014-2020 European Common Agricultural Policy (CAP) included provisions for support for risk management tools under Pillar II on Rural Development through the adoption of EU Regulation No 1305/2013.…”
Section: What Is the Role For Government?mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, what is "catastrophic" is less useful as an absolute measure and more related to specific characteristics of the crop/region in question, keeping in mind that these conditions may be changing due to climate change. 6 Other international negotiations are also affecting development of (and support for) risk management policy tools. Specifically, the 2014-2020 European Common Agricultural Policy (CAP) included provisions for support for risk management tools under Pillar II on Rural Development through the adoption of EU Regulation No 1305/2013.…”
Section: What Is the Role For Government?mentioning
confidence: 99%
“…If the amount of the co-payment exceeds the expected gain of the indemnity payment, producers have fewer incentives to deviate from best management practices 6. An alternative definition would be to describe "catastrophic" loss in terms of the individual loss distribution.…”
mentioning
confidence: 99%
“…A multitude of complicating factors, however, have been identified that challenge a sustainable multi-peril crop insurance market. Both adverse selection and extensive moral hazard have been shown to be significant issues (Just, Calvin, and Quiggin 1999;Wu, Goodwin, and Coble 2020). Additionally, farming tends to be regionally concentrated leading to high spatial correlation in risks which make it difficult for an actuarially sound private crop insurance market to emerge (Miranda and Glauber 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Even in developed countries, there is not much evidence to suggest that risk aversion among farmers is high enough to pay for purely private actuarial premiums (Goodwin, 2001; Smith and Glauber, 2012). Traditional indemnity‐based insurance programmes are subject to a myriad of well‐documented challenges, including information asymmetries in the form of moral hazard and adverse selection (Hazell, 1992; Morduch, 2006; Barnett and Mahul, 2007; Miranda and Farrin, 2012; Wu et al ., 2019) and ambiguity aversion (Elabed and Carter, 2015). They are also prone to other challenges, including high administrative costs (in particular, the cost of assessing losses), and covariate risks that translate into either higher risks of insolvency or which increase the cost of reinsurance.…”
Section: Introductionmentioning
confidence: 99%